Qur'anic exegesis of tafsir bil mathur - Ishak, Mohd. Shuhaimi (IACSIT Press, 2011)
Greek philosophy had introduced a methodology for interpretation known as allegory. Generally, it means that beneath the apparent meaning of a story is concealed another, more important meaning. This kind of interpretation was very common in Greek's antiquity and was later adopted by Muslim philosophers. Subsequently, Muslim Mufassirun (Qur'anic exegetes) gradually developed a methodology in the interpretation of the verses of the Qur'En. The aim of this paper is to illustrate the most acceptable and reliable fmm of Qur'anic exegesis known as tafsir bil mathur.